Regionalized video lesson: a teaching tool in the process of teaching the fundamental principle of counting (Revista BOEM, 2024)
This article presents an excerpt from an undergraduate research whose objective is to analyze the production of a video lesson with regionalized themes on Combinatorial Analysis content, with a view to its use as a teaching instrument inside and outside the classroom. This production is a continuation of the VideoMat Project, from PIBID/IFPA/Campus Belém. The study was established on the theoretical references of Ethnomathematics and Information and Communication Technologies, such as: D'Ambrósio (2002; 2009), Ponte (1995; 2000 ), Moran (1995),among others. This theoretical basis, with the support of PIBID, allowed the production of a high quality regionalized video lesson, recorded in the main tourist attraction of Pará (Ver-o-peso), with typical Pará language, situations, soundtrack, making the (future) student perceives content that is closer to their reality, with more meaning; promoting better fixation of the topics covered, being able to access it as many times, wherever and whenever you want. This video lesson is available on YouTube and can be used both by teachers, as a teaching tool, and by students. Thus, we hope to contribute so that education professionals can take advantage of this educational product in order to provide a more qualified education, with more meaning and that prepares them for life in a society that is increasingly technological.
Keywords: information and communication Technologies; video lessons; mathematics education; combinatorial analysis